2019
DOI: 10.1017/s0261444819000016
|View full text |Cite
|
Sign up to set email alerts
|

From research-as-practice to exploratory practice-as-research in language teaching and beyond

Abstract: Practitioner research is a flourishing area with a significant body of theoretical and empirical research, but often researchers remain isolated, unaware of impactful work by colleagues in related fields. Exploratory Practice (EP) is one innovative form, uniting creative pedagogy and research methods. The potential contributions have hitherto been neglected. EP's emphasis on puzzling and understanding is a means of demystifying occluded practices which place learners, teachers and researchers as co-investigato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 127 publications
0
34
0
1
Order By: Relevance
“…Teacher research in language teacher education Hanks (2019) suggests that TR literacy development can help not only educators examine puzzles about their own practices, but also position student-teachers as co-researchers, thereby opening up epistemological and pedagogical spaces for identity formation and (re)negotiation. In the context of this paper, identity broadly refers to how studentteachers see themselves as English teachers and how they wish to be perceived by others (Trent, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Teacher research in language teacher education Hanks (2019) suggests that TR literacy development can help not only educators examine puzzles about their own practices, but also position student-teachers as co-researchers, thereby opening up epistemological and pedagogical spaces for identity formation and (re)negotiation. In the context of this paper, identity broadly refers to how studentteachers see themselves as English teachers and how they wish to be perceived by others (Trent, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While the learner's voice is present in some of the analysed papers, the role of language teachers is subsumed by researchers, which prevents us from gaining a better grasp of how DDL can be normalised in contexts where language teachers work for non-HE institutions or they do not wish to carry out semi-experimental or mixed methods research. Arguably, action research or exploratory practice (Hanks, 2019) may increase the visibility of DDL across instructional contexts, languages and levels. As Warren (2016: 343) put it: "The difficulties encountered […] do not necessarily negate the DDL approach to language learning but rather underline the need for larger and more comprehensive corpora in order to better support corpus linguistics and data-driven learning".…”
Section: Discussionmentioning
confidence: 99%
“…Hence, teacher research not only became an instrument of reviewing their own professional practice but also constituted a space which integrated professional development, teaching, learning, and inquiry in which in which research is an inherent element of teachers' practice. While teacher research contributes to the cement the practice-research nexus (Hanks, 2019) through small-scale studies which prioritise specific circumstances, we may need reports which aim at (1) including rigorous and sophisticated description of research methods to secure transparency, (2) engaging in various types of triangulation to ensure trustworthiness and confirmability, (3) moving beyond, in several cases, participants' self-reporting, and (4) ensuring that concluding statements are robustly substantiated on the findings included in the paper. Possibly due to the limited length of the articles or authors' knowledge of research or preference for teacher research, authors do not seem to describe ethical procedures, acknowledge limitations or discuss their findings through critical eyes and cross-referencing the literature, which, in most cases, appears outdated or fails to recognise the works of other colleagues within Argentina.…”
Section: A Focus On Research Practicesmentioning
confidence: 99%
“…Two studies looked at (self-) assessment of TELL among tutors’ practices. According to these investigations (Innocentini & Forte, 2016; Massa, Morchio, & Schander, 2016), tutors should create and evaluate their online materials and their multimedia-based activities against criteria that are the result of consensus between tutors and learners. Regarding learners, Castiñeira and Mucci (2014, 2017) and Orta González and Castro (2017) found that while virtual learning environments (VLEs) were used for completing language learning skills, particularly reading and writing, they were also employed for interactional purposes among learners.…”
Section: Tellmentioning
confidence: 99%